STUDY OF DELIVERY PRACTICES OF OXYGEN BY HEALTHCARE PROFESSIONALS IN ACUTE EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Waheed, Aamir; Anwar, Aftab; Zaman, Syed Arif Saeed; Khaliq, Samia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To document the practices of our healthcare professionals (HCPs) about oxygen (O2) therapy in patients admitted with acute exacerbation of chronic obstructive pulmonary disease.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medicine, Sialkot Medical College, Sialkot, from Jul 2017 to Jan 2018.Methodology: 150 Health Care Professionals, working in emergency and intensive care units for more than 2 years, who administered supplemental oxygen to patients admitted with Acute Exacerbation of Chronic Obstructive Pulmonary Disease, were included in the study.Results: Of the 150 Health Care Professionals, 88 were staff nurses and 62 were doctors. 82.7% of Health Care Professionals knew the importance of controlled 2 delivery in patients of An acute exacerbation of chronic obstructive pulmonary disease. But only 66.9% actually practiced according to their knowledge/consultants prescription.Conclusion: Despite adequate knowledge of Health Care Professionals regarding oxygen supplementation in Acute Exacerbation of Chronic Obstructive Pulmonary Disease, their practices need to be improved. The culture of giving high concentration oxygen to patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease should be discouraged. Appropriate local protocols should be devised, prominently displayed and rigorously followed.